Pharmacogenomics in Drug Absorption and Its Implications for Personalized Medicine - Annisa Abdi Ghifari; Alauddin Syaifulanwar; Muhammad Yulis Hamidy (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Pharmacogenomics explores the impact of genetic differences on medication responsiveness. Drug absorption, affecting bioavailability and therapeutic efficacy, is controlled by genetic variations in transporters including P-gp and the SLC family. Genetic polymorphisms may alter plasma medication concentrations, affecting both safety and effectiveness. Understanding pharmacogenomics in drug absorption may encourage individualized therapy by modifying drug selection and dose according to genetic profiles. Despite implementation problems, pharmacogenomics offers potential for safer and more effective medications.